Strategi Pemberdayaan Masyarakat Penyandang Disabilitas Melalui Kelas Literasi oleh Dinas Perpustakaan dan Kearsipan Kota Salatiga - Nurhidayah, Rachmadita (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
The initiation of training activities through the Literacy Class at the Salatiga City Regional Library received appreciation from the National Library of the Republic of Indonesia for having a positive impact on the welfare of Persons with Disabilities. This study aims to analyze the strategy carried out by the Salatiga City Library and Archives Office in empowering Persons with Disabilities through Literacy Classes using the theory of empowerment strategies with the 5P approach according to Edi Suharto, namely enablement, strengthening, protecting, supporting, and maintaining. The type of research used is qualitative descriptive. This research uses data collection techniques carried out by observation, interviews, and documentation. The results of the study show that in the aspect of feasibility, organizing Literacy Classes involving Persons with Disabilities and collaborating with local communities, entrepreneurs, artists, and academics. In the strengthening aspect, simple materials and practices are provided according to the needs of Persons with Disabilities. In the aspect of protection, organizing a literacy exhibition has increased the awareness of the wider community about the potential of Persons with Disabilities. In the aspect of support, assistance is provided one by one and in stages, and is supported by facilities and motivation. In terms of maintenance, monitoring the development of Persons with Disabilities has not been carried out comprehensively, although some of them have received tangible benefits from the Literacy Class, such as business opportunities that support the welfare of life.